PEMBERDAYAAN MASYARAKAT DESA LANCAR MELALUI PENGUATAN LITERASI AL-QUR’AN BERBASIS METODE YANBU’UL QUR’AN - Rosi, Fauzi Fathur; Fauzan, Fauzan (Universitas Al-Amien Prenduan, 2024)
The low level of Quran literacy among the people of Lancar Village, Larangan Subdistrict, Pamekasan Regency is a fundamental problem in strengthening religious values. This condition is caused by a shortage of teachers, the lack of a systematic learning method, and the community's lack of motivation to study the Quran continuously. To address this problem, the community service team implemented a community empowerment program through strengthening Quran literacy based on the Yanbu'ul Quran method. This method was chosen because it has a clear, tiered, and effective system for improving the ability to read the Quran with tartil. The community service activities were carried out in three main stages, namely: (1) analysis of community needs through observation and interviews; (2) training and mentoring of Quran teachers on the application of the Yanbu'ul Qur'an method; and (3) Quran literacy classes involving children, teenagers, and adults. The implementation method used a participatory community development approach, in which the community became the main subject in the learning process and activity management. The results of the community service showed a significant increase in the community's ability to read the Qur'an, especially in terms of pronunciation of letters, accuracy of tajwid, and increased interest in participating in religious activities. In addition, the formation of mosque-based Qur'an study groups was the first step towards community independence in maintaining the culture of Qur'an literacy.